The Effect Of Liquidity, Asset Management, Sales Growth, And Good Corporate Governance On Company Value In The Automotive And Components Subsector Periode 2017 – 2024 - Theresia Aulia Pasaribu; Ramses Pakpahan (Journal of Accounting and Auditing, 2025)
Purpose – This study aims to obtain empirical evidence on the influence of liquidity, asset management, sales growth, and good corporate governance on company value. Design/methodology/approach –This study uses a quantitative research design. The sample consists of six automotive and component companies listed on the Indonesia Stock Exchange from 2017 to 2024. The analysis technique used to test the hypotheses is multiple regression analysis using SEM-Smart PLS. Findings – The results of this study found that Asset Management has a positive effect on Firm Value, as does Good Corporate Governance. Meanwhile, Sales Growth has a negative effect on Firm Value, and Liquidity has no effect on Firm Value. Research limitations/implications – The research discussrs Company Financial Liquidity, Asset Management, Sales Growth, and Good Corporate Governance wich focuses on automotive and componens sub sektor. This research uses an annual report periode 2017-2024.